"Getting It Right: Creating Partnerships for Change": Developing a Framework for Integrating Aboriginal and Torres Strait Islander Knowledges in Australian Social Work Education - Young, S.; Zubrzycki, J.; Green, S.; Jones, V.; Stratton, K.; Bessarab, Dawn (2013)
This article proposes a theoretical framework for integrating Aboriginal and Torres Strait Islander knowledges in Australian social work education as a central focus of the Getting it Right: Creating Partnerships for Change project. This article presents analysis from a literature review to suggest ways Australian schools of social work can adapt their curriculum in order to ensure that Aboriginal and Torres Strait Islander knowledges and practices occupy central and equally acknowledged positions in the teaching and learning experiences of social work students. The framework incorporates epistemological equality, Aboriginal and Torres Strait Islander-centered social work, cultural responsiveness, and indigenous pedagogy. © 2013 Copyright Taylor and Francis Group, LLC.